C++ by Dissection - Pohl, Ira (Addison Wesley, 2011)
C++ by Dissection presents a thorough introduction to the programming process by carefully developing working programs to illuminate key features of the C++ programming language. This book presents the concepts of the programming process using the "dissection" method, the hallmark feature that has made Ira Pohl's C and Java books of the "By Dissection" series so popular. Dissection is a unique pedagogical tool first developed by the author to point out key features of program code. It is similar to a structured walk-through of the code, with the intention of explaining newly encountered programming elements and idioms as found in working code. The book includes a CD-ROM containing a compiler and an electronic version of the book that allows readers to search, take notes, and highlight right on their computer. Each chapter presents a number of carefully explained programs, which lead the reader in a holistic manner to ever-improving programming skills. Right from the start, the reader is introduced to complete programs, and at an early point in the book, the reader is introduced to writing functions as a major feature of structured programming. It contains four to seven small code dissections per chapter, and then each chapter culminates with a larger, extended code dissection. "Software Engineering" sections in each chapter reinforce sound software engineering skills. The book assumes no programming background and can be used by first-time computer users or by experienced programmers who are transitioning to C++.